Inequality, fairness and social capital [dataset] - Fehr, Dietmar; Rau, Hannes; Trautmann, Stefan T.; Xu, Yilong (Universität, 2022)
Inequality is often associated with negative societal consequences, but identifying a causal relationship is a daunting task. We provide evidence o...
Gesehen am 08.04.2022
Keywords: Forschungsdaten; Datenbank